Analisis Kriminologi Kasus Kristen Gray: Pelanggaran Peraturan Pandemi dan Penyalahgunaan Izin Tinggal Keimigrasian di Indonesia - Nugroho, Agung Widi; Rabbani, Ahmad Akbar; Ristoka, Alvin Tuah (Universitas Batanghari Jambi, 2024)
This journal tries to discuss the Kristen Gray case from the perspective of a criminological approach. Criminology is a scientific discipline that is used to understand and overcome crimes that occur in society by studying the origins, causes and impacts of criminal behavior as well as the justice system for these criminal acts. Kristen Gray is a foreign citizen who comes from the United States, she became controversial because of statements on her personal social media which promoted and invited other foreign nationals to follow her, where she lives in Bali cheaply but can feel luxury in the midst of the COVID-19 Pandemic crisis and stating that Indonesia is a country that is friendly to the LGBT community or people, meanwhile in Indonesia itself, this issue is still very taboo. After being checked by immigration officers, it was discovered that he was also working in Indonesia, namely selling electronic books and opening a consulting service on how to enter Indonesia in the midst of the COVID-19 pandemic illegally, at which time human movement was strictly restricted to reduce the spread of this virus. Based on this, he and his LGBT partner were finally deported from Indonesia for allegedly violating Article 75 paragraph (1) of Law no. 6 of 2011 concerning Immigration, which in essence he is suspected of not complying with the laws currently in force in Indonesia and disrupting public notifications. The case of Kristen Gray was studied using theories in criminology, namely Opportunity Theory, Hedonistic Psychology Theory, and Differential Association Theory. Differential Association Theory is used as the reason why Kristen Gray's case must be immediately handled by local immigration authorities.